2021
DOI: 10.1039/d1nj00619c
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assemblies involving biologically relevant antiparallel π-stacking and unconventional solvent driven structural topology in maleato and fumarato bridged Zn(ii) coordination polymers: antiproliferative evaluation and theoretical studies

Abstract: Two new coordination polymers of Zn(II) viz.; {[Zn(Hdmpz)2(μ-male)]•(MeOH)(H2O)}n (1) and [Zn(3-AMpy)2(μ-fum)(H2O)2]n (2) (where, Hdmpz = 3,5-dimethyl pyrazole, male = maleate, fum = fumarate, 3-AMpy = 3-aminopyridine) have been synthesized and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 146 publications
0
4
0
Order By: Relevance
“…Although the precise cellular mechanism of MTT reduction into formazan is still unknown, it is believed that the reduction of MTT takes place with the NADH or other reducing molecules which transfer electrons to MTT. 75 The number of viable cells after 24 hours of treatment with compounds 1 and 2 can be estimated by measuring absorbance at 570 nm in a microplate reader after solubilization with isopropanol. 76 The results of the cell viability assay revealed that compounds 1 and 2 showed significant concentration dependent ( P ≤ 0.05) cytotoxicity in the DL cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the precise cellular mechanism of MTT reduction into formazan is still unknown, it is believed that the reduction of MTT takes place with the NADH or other reducing molecules which transfer electrons to MTT. 75 The number of viable cells after 24 hours of treatment with compounds 1 and 2 can be estimated by measuring absorbance at 570 nm in a microplate reader after solubilization with isopropanol. 76 The results of the cell viability assay revealed that compounds 1 and 2 showed significant concentration dependent ( P ≤ 0.05) cytotoxicity in the DL cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Research interest has surged in the investigation of transition metal coordination compounds that incorporate organic ligands, driven by their captivating structural arrangements and intricate network architectures [1][2][3][4][5][6][7]. The design, synthesis and development of metal-organic compounds with specific dimensionalities hinge upon diverse synthetic parameters, including metal-ion coordination with organic ligands, choice of solvent and reaction conditions [8][9][10][11][12][13][14][15][16]. Multi-component compounds, which are crystalline materials composed of two or more components (ions, atoms or molecules) in the same crystal lattice, have received remarkable attention in crystal engineering due to the evolving role of solid state chemistry in drug industries, electronic devices and synthetic organic chemistry [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] There are many data demonstrating the antitumor properties of various zinc compounds. [16][17][18][19] The reports on the ability of zinc complexes to induce apoptosis in breast cancer stem cells are intriguing since these cells are characterized by high drug resistance and are an extremely promising target for antitumor therapy. 20,21 The use of gold in medicine dates back to the 19 th century in the treatment of tuberculosis and rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%